CPR News. Issue 11 (December 2016) - Bleemer, Russ
Abstract : The International Institute for Conflict Prevention and Resolution noted the Nov. 7 passing of former U.S. Attorney General Janet Reno, expressing sympathy to her family, friends and colleagues, on its website and in social media.